Nominal species of Australasian/Oceanian Sarcophagidae proposed by P.J.M. Macquart (Insecta: Diptera) - Pape, Thomas (Zootaxa, 2008)
The six nominal species of Australasian/Oceanian Sarcophagidae proposed by Pierre Justin Marie Macquart are revised. Five nominal species enter into new synonymy, one remains unplaced. Lectotypes are designated for Sarcophaga assimilis Macquart, 1851 and Sarcophaga aurifrons Macquart, 1851. Sarcophaga sigma Johnston & Tiegs, 1921 is resurrected from synonymy with S. aurifrons.